Trauma of Unemployment on Nigerians - Nwazonobi, Patricia Ebere; Eboyem, Abraham O. (EBSU Journal of Social Sciences and Humanities, 2021)
Any living religion or government must not only make pronouncements on current human and social problems but must provide solutions as well especially on the trauma of unemployment on Nigeria. Relevant textbooks, journals, personal experiences and observations would be explored to showcase the trauma of unemplo yment on Nigerians. Consequentialist theory will also be applied to assess the ethical implications. About eighty percent of these young people are either unemployed or underemployed and this makes many observers to predict that the Nigeria youthful population is like a time bomb waiting to be detonated. However, without good monetary policy and fiscal policy, and without good governance and transparency, the Nigeria economy will continue to shrink with high unemployment, poverty and crime. Unemployment is bad because it is the root of poverty, rape of moral culture, corruption, political sychophancy and thuggery, armed robbery and armed conflicts, terrorism and militancy, proliferation of religions and religious economy in Nigeria today.